Water balance - stream water level and discharge from Erken Catchment, Stensta - outlet, 2006-01-02–2025-12-01 - Erken Laboratory (Uppsala University, 2026)
Stream water level measurements and discharge calculations from streams participating in the SITES Water and station base program including a constantly validated stream discharge relation curve. For further information on calculations and installation read COMMENT in the header of the data set, which guides to related document.
Erken Laboratory (2026). Water balance - stream water level and discharge from Erken Catchment, Stensta - outlet, 2006-01-02–2025-12-01 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/8nN_PfzxrgmZJ2PYB7XNPLpF
Keywords: Erken Laboratory; Discharge; Inland waters; Stream; Water level gauges; Time instant; Time instant; Stream level; Stream level; Water temperature; Water temperature; Electrical conductivity; Electrical conductivity; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap